Ultra-high performance concrete based on surface modified steel fibers and preparation method thereof

By coating graphene oxide on the surface of steel fibers, electrophoretic deposition technology is used to enhance the bonding between the fiber and the concrete matrix, the problem of insufficient bonding strength between the steel fiber and the matrix is ​​solved, and the mechanical properties of the concrete are significantly improved.

CN120574003APending Publication Date: 2025-09-02SUZHOU UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510901759.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-01
Publication Date
2025-09-02

AI Technical Summary

Technical Problem

In existing ultra-high performance concrete, the interface bonding strength between steel fibers and the substrate is insufficient, resulting in the fiber being easily pulled out and failing to fully utilize the advantages of high tensile strength.

Method used

Electrophoretic deposition technology is used to coat graphene oxide on the surface of steel fibers to form a rough, highly surfactant coating, which enhances the physical friction and chemical bonding between the fibers and the concrete matrix.

Benefits of technology

The bonding strength of the fiber-matrix interface is significantly improved, and the tensile and flexural strength of ultra-high performance concrete is improved, with an increase of 15.4% and 35.6% respectively.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120574003A_ABST
    Figure CN120574003A_ABST
Patent Text Reader

Abstract

The invention relates to ultra-high performance concrete based on surface modified steel fibers and a preparation method of the ultra-high performance concrete, and belongs to the technical field of building materials. In order to solve the problem of insufficient bonding strength between the existing steel fiber for the ultra-high performance concrete and a matrix, the invention provides the ultra-high performance concrete based on the surface modified steel fiber, which comprises the following components: Portland cement, silica fume, river sand, the surface modified steel fiber, a water reducing agent and water. The graphene oxide is uniformly deposited on the surface of the steel fiber through an electrophoretic deposition technology to form a rough coating with high surface activity. According to the coating, physical friction and chemical bonding effects between the steel fibers and a concrete matrix can be effectively improved by changing physical and chemical characteristics of the surfaces of the steel fibers, and the bonding strength of a fiber-matrix interface is remarkably enhanced, so that the macroscopic mechanical property of the ultra-high-performance concrete is improved, and the service life of the ultra-high-performance concrete is prolonged. The tensile strength of the ultra-high performance concrete is improved by 15.4% compared with that before steel fiber surface modification, and the breaking strength is improved by 35.6%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of building materials, and in particular relates to an ultra-high performance concrete based on surface-modified steel fibers and a preparation method thereof. Background Art

[0002] Ultra-high performance concrete (UHPC), with its exceptional mechanical properties and durability, is widely used in major strategic projects such as military defense and water conservancy projects. In this material system, steel fibers serve as a key reinforcing component, significantly improving the tensile, flexural, impact, and fatigue resistance of concrete by bridging cracks. However, the smooth surface of conventional steel fibers results in insufficient interfacial bonding strength with the concrete matrix. When subjected to stress, the fibers are prone to pullout failure, preventing them from fully realizing their high tensile strength.

[0003] An important means to solve the above problems is to modify the surface of steel fibers, among which the nanomaterial coating method has been widely recognized. This method constructs a coating structure with nanoscale roughness or specific chemical functional groups by attaching and growing nanomaterials on the surface of steel fibers, which can effectively enhance the friction and chemical adhesion between steel fibers and the substrate. However, the existing nanocoating process usually has high requirements on parameters such as reaction solution concentration, temperature, and pH value, and the operation process is complicated and cumbersome. This dependence on high-precision environment and strict operating procedures has led to major obstacles in the practical application of the technology. Therefore, it is necessary to develop a convenient and efficient method for modifying steel fibers with nanocoating to achieve effective improvement in the performance of ultra-high performance concrete. Summary of the Invention

[0004] In order to solve the problem of insufficient bonding strength between steel fibers and matrix used in existing ultra-high performance concrete, the present invention provides an ultra-high performance concrete based on surface-modified steel fibers and a preparation method thereof.

[0005] The technical solution of the present invention:

[0006] An ultra-high performance concrete based on surface-modified steel fibers contains the following components, measured by weight: 800 parts of Portland cement, 160-200 parts of silica fume, 864-1000 parts of river sand, 141.2-183.7 parts of surface-modified steel fibers, 19.2-25 parts of a water reducer, and 172.8-200 parts of water.

[0007] Furthermore, the surface-modified steel fiber uses electrophoretic deposition technology to achieve controllable coating of graphene oxide on the surface of the steel fiber, and the specific method is as follows:

[0008] Step 1: Steel fiber pretreatment:

[0009] The steel fiber is placed in anhydrous ethanol, ultrasonically cleaned, and then dried for later use;

[0010] Step 2: Electrode assembly and configuration:

[0011] Steel fibers are evenly laid on a stainless steel mesh as a deposition electrode, the deposition electrode is horizontally suspended in the middle of the electrolytic cell, and the deposition electrode is connected to the positive electrode of a DC power supply via a copper wire. Two graphite plates are vertically symmetrically placed on both sides of the deposition power supply as counter electrodes, and the counter electrodes are connected to the negative electrode of the DC power supply via a copper wire;

[0012] Step 3: Electrophoretic deposition:

[0013] injecting the graphene oxide aqueous dispersion into the electrolytic cell so that the liquid level completely submerges the deposition electrode; and performing electrophoretic deposition at a constant voltage;

[0014] Step 4: Post-processing:

[0015] After the electrophoretic deposition is completed, the surface-modified steel fiber is obtained, which is vacuum-dried to a constant weight for later use.

[0016] Furthermore, the steel fiber in step 1 is a copper-plated straight steel fiber with a length of 13 mm and a diameter of 0.2 mm.

[0017] Furthermore, the steel fiber in step 1 is ultrasonically cleaned in anhydrous ethanol for 10 to 30 minutes.

[0018] Furthermore, the concentration of the graphene oxide aqueous dispersion in step 3 is 0.1-0.3 mg / ml.

[0019] Furthermore, the voltage of the electrophoretic deposition in step 3 is 20-30 V, and the deposition time is 10-40 min.

[0020] Furthermore, during the deposition process in step three, the power supply was turned off every 5 minutes, and the stainless steel mesh of the deposition electrode was gently shaken to rearrange the positions of the steel fibers.

[0021] Furthermore, the temperature of the vacuum drying in step 4 is 40-60°C.

[0022] A method for preparing ultra-high performance concrete based on surface-modified steel fibers comprises adding silicate cement, silica fume, and river sand into a stirring device and dry-mixing for 5 minutes; then pouring a uniform mixed solution of a water reducer and water and continuing to stir for 10 minutes; further adding the surface-modified steel fibers and stirring for 5 minutes to obtain ultra-high performance concrete.

[0023] Furthermore, the curing method of the ultra-high performance concrete is: pouring the stirred ultra-high performance concrete into a mold, placing it in a 90° C. curing box for steam curing for 2-3 days.

[0024] Beneficial effects of the present invention:

[0025] This paper proposes an ultra-high-performance concrete based on surface-modified steel fibers. Graphene oxide is uniformly deposited onto the steel fiber surface via electrophoretic deposition, forming a rough, highly surface-active coating. This coating, by altering the physical and chemical properties of the steel fiber surface, effectively improves the physical friction and chemical bonding between the steel fiber and the concrete matrix, significantly enhancing the fiber-matrix interfacial bond strength. This, in turn, improves the macroscopic mechanical properties of the ultra-high-performance concrete, resulting in a 15.4% increase in tensile strength and a 35.6% increase in flexural strength compared to pre-modified steel fiber surfaces.

[0026] The steel fiber modification method proposed in this paper utilizes proven electrophoresis equipment, offering simple operation, strong process controllability, and no need for complex pretreatment. The primarily water-based medium is environmentally friendly. The process exhibits excellent stability and reproducibility, providing a competitive technical path for the large-scale mass production of surface-modified steel fibers. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The scanning electron microscope image and energy spectrum analysis image of the steel fiber surface before surface modification;

[0028] Figure 2 The scanning electron microscope image and energy spectrum analysis image of the surface of the surface-modified steel fiber prepared in Example 1;

[0029] Figure 3 1 is a tensile load-slip curve of steel fiber in concrete of Example 1 and Comparative Example 1;

[0030] Figure 4 1 is a comparison chart of the tensile strength of concrete of Example 1 and Comparative Example 1;

[0031] Figure 5 The figure is a comparison of the flexural strength of the concrete of Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is further described below with reference to the embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention shall be included in the scope of protection of the present invention. The process equipment or devices not specifically noted in the following examples are all conventional equipment or devices in the art. Unless otherwise specified, the raw materials used in the examples of the present invention can be obtained commercially; unless otherwise specified, the technical means used in the examples of the present invention are all conventional means well known to those skilled in the art.

[0033] Example 1

[0034] This embodiment provides an ultra-high performance concrete based on surface-modified steel fiber, which contains the following components, by weight: 800 parts of Portland cement, 200 parts of silica fume, 900 parts of river sand, 147 parts of surface-modified steel fiber, 25 parts of water reducer and 180 parts of water.

[0035] In this embodiment, the surface-modified steel fiber uses electrophoretic deposition technology to achieve controllable coating of graphene oxide on the steel fiber surface. The specific method is as follows:

[0036] Step 1: Steel fiber pretreatment:

[0037] The copper-plated straight steel fiber is placed in anhydrous ethanol, ultrasonically cleaned for 10 to 30 minutes, and then dried for use; the copper-plated straight steel fiber used in this embodiment has a length of 13 mm, a diameter of 0.2 mm, and a tensile strength of 2850 MPa.

[0038] Step 2: Electrode assembly and configuration:

[0039] Steel fibers are evenly laid on a stainless steel mesh as a deposition electrode, the deposition electrode is horizontally suspended in the middle of the electrolytic cell, and the deposition electrode is connected to the positive electrode of a DC power supply via a copper wire. Two graphite plates are vertically symmetrically placed on both sides of the deposition power supply as counter electrodes, and the counter electrodes are connected to the negative electrode of the DC power supply via a copper wire;

[0040] Step 3: Electrophoretic deposition:

[0041] A 0.2 mg / ml aqueous dispersion of graphene oxide was injected into the electrolytic cell until the liquid level completely submerged the deposition electrode. Electrophoretic deposition was performed at a constant voltage of 30 V for 30 minutes. During the deposition process, the power was turned off every 5 minutes, and the stainless steel mesh of the deposition electrode was gently shaken to rearrange the position of the steel fibers.

[0042] Step 4: Post-processing:

[0043] After the electrophoretic deposition was completed, the surface-modified steel fibers were obtained and vacuum-dried at 50°C to a constant weight for later use.

[0044] This example also provides a method for preparing ultra-high performance concrete based on surface-modified steel fibers. Portland cement, silica fume, and river sand are added to a mixing pot and dry-mixed for 5 minutes. A uniform mixture of a water reducer and water is then added and stirred for 10 minutes. The surface-modified steel fibers are then added and stirred for 5 minutes to produce ultra-high performance concrete. The resulting ultra-high performance concrete slurry is poured into a mold and steam-cured in a 90°C curing oven for 3 days. The resulting concrete material is referred to as Example 1.

[0045] The surface morphology and elemental composition of steel fibers before and after surface modification were analyzed using electron scanning microscopy and energy dispersive spectrometer. Figure 1 and Figure 2 As shown in the figure, the surface of the untreated steel fiber is smooth, and the main elements are Fe and Cu; the surface of the surface-modified steel fiber is covered with a wrinkled graphene oxide coating, and a large amount of C and O elements are detected.

[0046] Example 2

[0047] This embodiment provides an ultra-high performance concrete based on surface-modified steel fiber, which contains the following components, by weight: 800 parts of Portland cement, 160 parts of silica fume, 1000 parts of river sand, 160 parts of surface-modified steel fiber, 20 parts of water reducer and 190 parts of water.

[0048] In this embodiment, the surface-modified steel fiber uses electrophoretic deposition technology to achieve controllable coating of graphene oxide on the steel fiber surface. The specific method is as follows:

[0049] Step 1: Steel fiber pretreatment:

[0050] The copper-plated straight steel fiber is placed in anhydrous ethanol, ultrasonically cleaned for 10 to 30 minutes, and then dried for use; the copper-plated straight steel fiber used in this embodiment has a length of 13 mm, a diameter of 0.2 mm, and a tensile strength of 2850 MPa.

[0051] Step 2: Electrode assembly and configuration:

[0052] Steel fibers are evenly laid on a stainless steel mesh as a deposition electrode, the deposition electrode is horizontally suspended in the middle of the electrolytic cell, and the deposition electrode is connected to the positive electrode of a DC power supply via a copper wire. Two graphite plates are vertically symmetrically placed on both sides of the deposition power supply as counter electrodes, and the counter electrodes are connected to the negative electrode of the DC power supply via a copper wire;

[0053] Step 3: Electrophoretic deposition:

[0054] A 0.1 mg / ml aqueous dispersion of graphene oxide was injected into the electrolytic cell until the liquid level completely submerged the deposition electrode. Electrophoretic deposition was performed at a constant voltage of 20 V for 20 minutes. During the deposition process, the power was turned off every 5 minutes, and the stainless steel mesh of the deposition electrode was gently shaken to rearrange the position of the steel fibers.

[0055] Step 4: Post-processing:

[0056] After the electrophoretic deposition was completed, the surface-modified steel fibers were obtained and vacuum-dried at 40°C to a constant weight for later use.

[0057] This example also provides a method for preparing ultra-high performance concrete based on surface-modified steel fibers. Portland cement, silica fume, and river sand are added to a mixing pot and dry-mixed for 5 minutes. A uniform mixture of a water reducer and water is then added and stirred for 10 minutes. The surface-modified steel fibers are then added and stirred for 5 minutes to produce ultra-high performance concrete. The resulting ultra-high performance concrete slurry is poured into a mold and steam-cured in a 90°C curing chamber for 3 days.

[0058] Example 3

[0059] This embodiment provides an ultra-high performance concrete based on surface-modified steel fiber, which contains the following components, by weight: 800 parts of Portland cement, 170 parts of silica fume, 900 parts of river sand, 170 parts of surface-modified steel fiber, 25 parts of water reducer and 200 parts of water.

[0060] In this embodiment, the surface-modified steel fiber uses electrophoretic deposition technology to achieve controllable coating of graphene oxide on the steel fiber surface. The specific method is as follows:

[0061] Step 1: Steel fiber pretreatment:

[0062] The copper-plated straight steel fiber is placed in anhydrous ethanol, ultrasonically cleaned for 10 to 30 minutes, and then dried for use; the copper-plated straight steel fiber used in this embodiment has a length of 13 mm, a diameter of 0.2 mm, and a tensile strength of 2850 MPa.

[0063] Step 2: Electrode assembly and configuration:

[0064] Steel fibers are evenly laid on a stainless steel mesh as a deposition electrode, the deposition electrode is horizontally suspended in the middle of the electrolytic cell, and the deposition electrode is connected to the positive electrode of a DC power supply via a copper wire. Two graphite plates are vertically symmetrically placed on both sides of the deposition power supply as counter electrodes, and the counter electrodes are connected to the negative electrode of the DC power supply via a copper wire;

[0065] Step 3: Electrophoretic deposition:

[0066] A 0.3 mg / ml aqueous dispersion of graphene oxide was injected into the electrolytic cell until the liquid level completely submerged the deposition electrode. Electrophoretic deposition was performed at a constant voltage of 30 V for 10 minutes. During the deposition process, the power was turned off every 5 minutes, and the stainless steel mesh of the deposition electrode was gently shaken to rearrange the position of the steel fibers.

[0067] Step 4: Post-processing:

[0068] After the electrophoretic deposition was completed, the surface-modified steel fibers were obtained and vacuum-dried at 60°C to a constant weight for later use.

[0069] This example also provides a method for preparing ultra-high performance concrete based on surface-modified steel fibers. Portland cement, silica fume, and river sand are added to a mixing pot and dry-mixed for 5 minutes. A uniform mixture of a water reducer and water is then added and stirred for 10 minutes. The surface-modified steel fibers are then added and stirred for 5 minutes to produce ultra-high performance concrete. The resulting ultra-high performance concrete slurry is poured into a mold and steam-cured in a 90°C curing chamber for 3 days.

[0070] Example 4

[0071] This embodiment provides an ultra-high performance concrete based on surface-modified steel fiber, which contains the following components, by weight: 800 parts of Portland cement, 180 parts of silica fume, 950 parts of river sand, 180 parts of surface-modified steel fiber, 20 parts of water reducer and 180 parts of water.

[0072] In this embodiment, the surface-modified steel fiber uses electrophoretic deposition technology to achieve controllable coating of graphene oxide on the steel fiber surface. The specific method is as follows:

[0073] Step 1: Steel fiber pretreatment:

[0074] The copper-plated straight steel fiber is placed in anhydrous ethanol, ultrasonically cleaned for 10 to 30 minutes, and then dried for use; the copper-plated straight steel fiber used in this embodiment has a length of 13 mm, a diameter of 0.2 mm, and a tensile strength of 2850 MPa.

[0075] Step 2: Electrode assembly and configuration:

[0076] Steel fibers are evenly laid on a stainless steel mesh as a deposition electrode, the deposition electrode is horizontally suspended in the middle of the electrolytic cell, and the deposition electrode is connected to the positive electrode of a DC power supply via a copper wire. Two graphite plates are vertically symmetrically placed on both sides of the deposition power supply as counter electrodes, and the counter electrodes are connected to the negative electrode of the DC power supply via a copper wire;

[0077] Step 3: Electrophoretic deposition:

[0078] A 0.2 mg / ml aqueous dispersion of graphene oxide was injected into the electrolytic cell until the liquid level completely submerged the deposition electrode. Electrophoretic deposition was performed at a constant voltage of 20 V for 40 minutes. During the deposition process, the power was turned off every 5 minutes, and the stainless steel mesh of the deposition electrode was gently shaken to rearrange the position of the steel fibers.

[0079] Step 4: Post-processing:

[0080] After the electrophoretic deposition was completed, the surface-modified steel fibers were obtained and vacuum-dried at 50°C to a constant weight for later use.

[0081] This example also provides a method for preparing ultra-high performance concrete based on surface-modified steel fibers. Portland cement, silica fume, and river sand are added to a mixing pot and dry-mixed for 5 minutes. A uniform mixture of a water reducer and water is then added and stirred for 10 minutes. The surface-modified steel fibers are then added and stirred for 5 minutes to produce ultra-high performance concrete. The resulting ultra-high performance concrete slurry is poured into a mold and steam-cured in a 90°C curing chamber for 3 days.

[0082] Comparative Example 1

[0083] This comparative example provides a conventional concrete containing the following components, by weight: 800 parts Portland cement, 200 parts silica fume, 900 parts river sand, 147 parts untreated copper-coated straight steel fibers, 25 parts water reducer, and 180 parts water. The copper-coated straight steel fibers in this comparative example have a length of 13 mm, a diameter of 0.2 mm, and a tensile strength of 2850 MPa.

[0084] This comparative example also provides a method for preparing concrete. Portland cement, silica fume, and river sand are added to a mixing pot and dry-mixed for 5 minutes. A uniform mixture of a water reducer and water is then added and stirred for 10 minutes. Surface steel fiber is then added and stirred for 5 minutes to produce concrete. The resulting concrete slurry is poured into a mold and steam-cured in a 90°C curing oven for 3 days. The resulting concrete material is designated as the baseline.

[0085] The steel fibers in the concrete materials obtained after curing for 3 days in Example 1 and Comparative Example 1 were subjected to a single fiber pullout test. The results are as follows: Figure 3 As shown, the maximum pull-out force of a single steel fiber in Comparative Example 1 is 26.1 N, and the fiber-matrix interface bonding strength is 8.8 MPa. The maximum pull-out force of a single steel fiber in Example 1 can reach 30.5 N, and the interface bonding strength reaches 10.8 MPa, which is a 22.7% improvement over Comparative Example 1. This proves that graphene oxide coating can significantly improve the performance of the steel fiber-matrix interface.

[0086] The tensile strength and flexural strength of the concrete materials obtained after curing for 3 days in Example 1 and Comparative Example 1 were tested. Figure 4 and Figure 5 As shown, the tensile strength of the concrete material of Comparative Example 1 is 9.6 MPa, and the flexural strength is 11.5 MPa; the tensile strength of the concrete material of Example 1 can reach 11.0 MPa, which is 15.4% higher than that of Comparative Example 1, and the flexural strength can reach 15.6 MPa, which is 35.6% higher than that of Comparative Example 1.

Claims

1. An ultra-high performance concrete based on surface-modified steel fiber, characterized in that: The composition comprises the following components in parts by weight: 800 parts of Portland cement, 160-200 parts of silica fume, 864-1000 parts of river sand, 141.2-183.7 parts of surface-modified steel fiber, 19.2-25 parts of water reducer and 172.8-200 parts of water.

2. The ultra-high performance concrete based on surface-modified steel fiber according to claim 1, characterized in that: The surface-modified steel fiber uses electrophoretic deposition technology to achieve controllable coating of graphene oxide on the surface of the steel fiber. The specific method is as follows: Step 1: Steel fiber pretreatment: The steel fiber is placed in anhydrous ethanol, ultrasonically cleaned, and then dried for later use; Step 2: Electrode assembly and configuration: Steel fibers are evenly laid on a stainless steel mesh as a deposition electrode, the deposition electrode is horizontally suspended in the middle of the electrolytic cell, and the deposition electrode is connected to the positive electrode of a DC power supply via a copper wire. Two graphite plates are vertically symmetrically placed on both sides of the deposition power supply as counter electrodes, and the counter electrodes are connected to the negative electrode of the DC power supply via a copper wire; Step 3: Electrophoretic deposition: injecting the graphene oxide aqueous dispersion into the electrolytic cell so that the liquid level completely submerges the deposition electrode; and performing electrophoretic deposition at a constant voltage; Step 4: Post-processing: After the electrophoretic deposition is completed, the surface-modified steel fiber is obtained, which is vacuum-dried to a constant weight for later use.

3. The ultra-high performance concrete based on surface-modified steel fiber according to claim 2, characterized in that: The steel fiber in step 1 is a copper-plated straight steel fiber with a length of 13 mm and a diameter of 0.2 mm.

4. The ultra-high performance concrete based on surface-modified steel fiber according to claim 3, characterized in that: The steel fiber in step 1 is ultrasonically cleaned in anhydrous ethanol for 10 to 30 minutes.

5. The ultra-high performance concrete based on surface-modified steel fiber according to claim 4, characterized in that: The concentration of the graphene oxide aqueous dispersion in step 3 is 0.1-0.3 mg / ml.

6. The ultra-high performance concrete based on surface-modified steel fiber according to claim 5, characterized in that: The voltage of the electrophoretic deposition in step 3 is 20-30 V, and the deposition time is 10-40 min.

7. The ultra-high performance concrete based on surface-modified steel fiber according to claim 6, characterized in that: Step 3: During the deposition process, turn off the power every 5 minutes and gently shake the stainless steel mesh of the deposition electrode to rearrange the position of the steel fibers.

8. The ultra-high performance concrete based on surface-modified steel fiber according to claim 7, characterized in that: The temperature of step 4 vacuum drying is 40-60°C.

9. A method for preparing ultra-high performance concrete based on surface-modified steel fibers according to any one of claims 1 to 8, characterized in that: Add silicate cement, silica fume and river sand into a mixing device and dry mix for 5 minutes; then pour in a uniform mixture of water reducer and water and continue stirring for 10 minutes; further add surface-modified steel fiber and stir for 5 minutes to obtain ultra-high performance concrete.

10. The method for preparing ultra-high performance concrete based on surface-modified steel fiber according to claim 9, characterized in that: The curing method of the ultra-high performance concrete is as follows: pouring the stirred ultra-high performance concrete into a mold, and placing the mold in a 90° C. curing box for steam curing for 2-3 days.